Estimates of class "A" pan evaporation in Brazil - Mota, Fernando Silveira; Agendes, Marisa Oliveira de Oliveira; Alves, Eliane Grala Pereira; Becker, Carmem Terezinha (Pesquisa Agropecuaria Brasileira, 1993)
The nomogram of Kohler et al. (1959), developed in the United State of America for the estimation of class "A" pan evaporation from solar radiation, dew point and wind movement was tested with data from five stations located in the main Brazilian climatic regions. Results show good agreement between estimated and measured pan evaporation. It was concluded that this nomogram may be applied to Brazilian conditions with good results.